PENGARUH LINGKUNGAN SEKOLAH DAN MOTIVASI BERWIRAUSAHA TERHADAP SIKAP KEWIRAUSAHAAN(Survei pada Siswa Kelas X Bisnis Daring dan Pemasaran di SMK Sangkuriang 1 Cimahi) - Mayang Damayanti, - (2022)
ABSTRACT Mayang Damayanti (1600592), "The Influence of the School Environment and Entrepreneurial Motivation on Entrepreneurship Attitudes (a Survey of 10th Graders of Online Businesses and Marketing at SMK Sangkuriang 1 Cimahi)". Under the guidance Prof. Dr. H. Hari Mulyadi,M.Si and Sulastri, S.Pd., M.Stat., MM. This study aims to determine the effect of the school environment and entrepreneurial motivation on entrepreneurial attitudes (a survey of 63 respondents in class X online business and marketing at SMK Sangkuriang 1 Cimahi). The design of this study was cross sectional using an explanatory approach through the explanatory survey method. with the data analysis technique used is path analysis (path analysis) with computer software SPSS version 25.0. the results of the study can be seen that 1) the description of the school environment is included in the conducive category. 2) description of entrepreneurial motivation is included in the sufficient category. 3) the description of the entrepreneurial attitude is included in the positive category. 4) the school environment has a positive and significant effect on entrepreneurial attitude. 5) entrepreneurship motivation has a positive and significant effect on entrepreneurial attitude. 6) school environment and entrepreneurial motivation have a positive and significant effect on entrepreneurial attitudes. From the results of hypothesis testing research, it can be seen that the influence of school environment and entrepreneurial motivation significantly influence entrepreneurial attitudes. Keywords: School Environment, Entrepreneurial Motivation and Entrepreneurial Attitude.